Prevalence of waterpipe smoking and its associated factors among adolescents aged 12–16 years in 73 countries/territories - Ma, Chuanwei; Yang, Hui; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Public Health, 2022)
To describe the recent prevalence of, and trends in, waterpipe smoking and to examine its associated factors among adolescents aged 12-16 years in 73 countries/territories (hereafter “countries”). Data from 72 countries that had conducted a Global Youth Tobacco Survey (GYTS) in 2010 -2019 and from the National Youth Tobacco Survey in the United States in 2019 were used to assess the recent prevalence of waterpipe smoking and to examine its associated factors among adolescents aged 12-16 years. Data from 38 countries that had carried out at least 2 surveys from 2000 to 2019 were used to determine trends in the prevalence of waterpipe smoking among adolescents. The recent prevalence of current waterpipe smoking (on ≥ 1 day during the past 30 days) among adolescents was 6.9% (95%CI 6.4-7.5). The prevalence was highest in the European region (10.9%, 9.9-11.8) and Eastern Mediterranean region (10.7%, 9.5-11.9), but lowest in the Western Pacific region (1.9%, 1.4-2.4). The prevalence of current waterpipe smoking increased or remained unchanged in 19 (50%) of 38 countries, but decreased in the remaining 19 countries (50%). Parental smoking, closest friends’ smoking, secondhand smoke exposure, tobacco advertisement exposure, not being taught the dangers of smoking, particularly cigarette smoking, were positively associated with adolescent waterpipe smoking. Waterpipe smoking among adolescents remains a major public health issue worldwide, especially in the regions of Europe and the Eastern Mediterranean. Effective prevention and control strategies and measures are needed to curb the epidemic of adolescent waterpipe smoking.